Rancangan tempatan Majlis Daerah Kubang Pasu, Kedah (2035) (Penggantian) - Asmawi, M. Zainora (PlanMalaysia, 2018)
The Local Plan is prepared to replace the present Local Plan. It covers the development strategies and proposal plans for district of Kubang Pasu, ranging from land use until environment. It has gone through the process of analysis and recommendation following the national framework of preparing Local Plan under the purview of PlanMalaysia@Kedah.